2017
DOI: 10.1007/s10509-017-3028-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing binary systems from rotating parent gas structures with different total masses

Abstract: In this paper we continue the investigation reported by Arreaga (2016) concerning the morphology of binary configurations obtained via the collapse of rotating parent gas structures with total masses in the range of M T = 1 to 5 M . Here we extend the mass range and consider the collapse of two uniform gas clumps of M T = 50 and 400 M , so that they also rotates rigidly in such a way that its approximate virial parameter takes the values of 0.5, 1.5, and 2.5 and their collapse is induced initially by implement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…There are several processes that have been proposed in the literature to play a role in setting the pristine fragmentation of a core, such as the magnetic field (e. g., Boss et al 2004; Vázquez-Semadeni et al 2005; Hennebelle et al 2011, Commerçon et al 2011; Fontani et al 2016), turbulent support (e. g., Zhang et al 2009, 2015; Wang et al 2011, 2014; Pillai et al 2011, Lu et al 2015), or the rotational-to-gravitational energy (e. g., Arreaga-Garcia 2017, Lim et al 2016). Recently, Palau et al (2014, 2015) have studied the aforementioned processes in a sample of 19 massive dense cores and found that the fragmentation level within cores of 0.1 pc is best correlated with the density structure of the cores, rather than with the non-thermal velocity dispersion (Palau et al 2015) or even the rotational-to-gravitational energy (Palau et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are several processes that have been proposed in the literature to play a role in setting the pristine fragmentation of a core, such as the magnetic field (e. g., Boss et al 2004; Vázquez-Semadeni et al 2005; Hennebelle et al 2011, Commerçon et al 2011; Fontani et al 2016), turbulent support (e. g., Zhang et al 2009, 2015; Wang et al 2011, 2014; Pillai et al 2011, Lu et al 2015), or the rotational-to-gravitational energy (e. g., Arreaga-Garcia 2017, Lim et al 2016). Recently, Palau et al (2014, 2015) have studied the aforementioned processes in a sample of 19 massive dense cores and found that the fragmentation level within cores of 0.1 pc is best correlated with the density structure of the cores, rather than with the non-thermal velocity dispersion (Palau et al 2015) or even the rotational-to-gravitational energy (Palau et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, several studies have been performed to investigate the properties of fragmentation in molecular clouds. These works have concentrated on the study of the physical processes that control fragmentation such as turbulence (Zhang et al 2009(Zhang et al , 2015Pillai et al 2011;Wang et al 2011Wang et al , 2014Lu et al 2015), disk fragmentation (e.g., Adams et al 1989;Kratter et al 2010;Vorobyov & Basu 2010), rotational fragmentation (e.g., Lim et al 2016;Arreaga-García 2017), stellar feedback (e.g., Krumholz et al 2007;Peters et al 2010;Myers et al 2013), and magnetic fields (e.g., Boss 2004;Vázquez-Semadeni et al 2005;Commerçon et al 2011a;Hennebelle et al 2011). On the other hand, a number of studies have found that the fragmentation of dusty cores seems to be related to the density of the cores (e.g., Gutermuth et al 2011;Lombardi et al 2013;Ragan et al 2013; Final reduced data are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, several studies have been performed to investigate the properties of fragmentation in molecular clouds. These works have concentrated on the study of the physical processes that control fragmentation such as turbulence (Zhang et al 2009Pillai et al 2011;Wang et al 2011Wang et al , 2014, disk fragmentation (e.g., Adams, Ruden & Shu 1989;Kratter et al 2010;Vorobyov & Basu 2010), rotational fragmentation (e.g., Lim et al 2016;Arreaga-García 2017), stellar feedback (e.g., Krumholz et al 2007;Peters et al 2010;Myers et al 2013), and magnetic fields (e.g., Boss 2004;Vázquez-Semadeni, Kim, & Ballesteros-Paredes 2005;Commerçon, Hennebelle & Henning 2011;Hennebelle et al 2011). On the other hand, a number of studies have found that the fragmentation of dusty cores seems to be related to the density of the cores (e.g., Gutermuth et al 2011;Lombardi, Lada & Alves 2013;Ragan, Henning & Beuther 2013;Imara 2015;Lee et al 2015;Mairs et al 2016;Nguyen-Luong et al 2016;Liu et al 2016;Pokhrel et al 2016Pokhrel et al , 2018Hacar, Tafalla & Alves 2017;Mercimek et al 2017;Alfaro & Román-Zúñiga 2018;Li et al 2019;Orkisz et al 2019;Sanhueza et al 2019;Sokol et al 2019;Svoboda et al 2019;Zhang et al 2019), indicating that the fragmentation of cores is consistent with a thermal...…”
Section: Introductionmentioning
confidence: 99%